Enabling Setting for Sustainable Village Tourism : Increasing the Empowerment of Beneficiary Communities - Amirul Mustofa; Eny Haryati; Litafira Syahadiyanti (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This study discusses the role of enabling setting in increasing the empowerment of beneficiary communities in Tamansari Tourism Village, Banyuwangi Regency. Enabling setting is understood as a supportive environment that includes inclusive policies, access to resources, community participation, and cultural and environmental preservation. The research was conducted with a qualitative approach through case studies, using in-depth interview techniques, participatory observation, and document studies. The results show that the empowerment of communities depends not only on increased economic income, but also on their ability to be actively involved in tourism management, safeguard local cultural values, and gain equitable access to training and information. Government support, partnerships with the private sector, and local initiatives are important factors in creating empowerment. However, challenges such as inequality of participation, limited digital access, and potential conflicts between community groups were also found. This study concludes that sustainable development of tourism villages must prioritize multi-stakeholder collaboration and strengthen local capacity equally. These findings make a practical contribution to the formulation of more inclusive policies and serve as a reference for the sustainable development of community-based tourism villages in Indonesia. Furthermore, the study highlights the critical role of continuous capacity building and knowledge sharing among community members to ensure long-term sustainability. By fostering an environment where local residents are equipped with the necessary skills and information, the community can better adapt to changing tourism trends and external pressures. Additionally, the integration of digital tools and platforms is recommended to bridge the information gap and enhance marketing efforts, thus expanding the reach of the tourism village. These strategies collectively support a more resilient and self-reliant community, capable of maintaining both economic growth and cultural integrity in the face of development challenges.